(untitled) (Research, Society and Development, 2021)
Objective: to validate a flowchart to articulate public health and supplement from the perspective of comprehensive care. Methodology: The study is part of the master’s research entitled: "construction and validation of a flowchart for articulation of public and supplementary health from the perspective of comprehensive care". It is an investigation of a methodological nature, which was composed of: PHASE I - semi-structured interviews; PHASE II -elaboration of the flowchart; and PHASE III - Content and Appearance Validation. After coding the material obtained in the interviews, analyses of classical and nvivo-supported category content were performed, whose data were used to make up the first version of the flowchart. The first version of the tool went through content and appearance validation. Results and Discussion: The results of the validations brought scores of 100% agreement of the Content Judges (CVI = 1.00) and classified the flowchart as "superior" according to the measure of the SAM instrument. From the return of the experts’ evaluations, the items accepted in the flowchart were maintained and the items that had notes were adjusted, generating the final version of the flowchart. Conclusion: The proposed flow is an innovative proposal for the Health System and intends to contribute to the routine systematization for the articulation of public and supplementary health, considering that currently the sectors are articulated primarily in the perspective of reimbursement to the SUS.